The Effect of Social Pressure and Lifestyle on the Financial Stability of FEBI Students at the State Islamic University of North Sumatra Who Use SPayLater - Desi Khairani Harahap; Atika; Purnama Ramadani Silalahi (Universitas Negeri Padang, 2026)
The rapid growth of buy-now, pay-later services has made it easier for students to access digital credit. However, few studies have examined how this affects financial stability, particularly among SPayLater users in Islamic economics education. This study examines how social pressure and lifestyle affect the financial stability of students in the Faculty of Islamic Economics and Business at the State Islamic University of North Sumatra who use SPayLater services. We gathered data through a quantitative survey of 100 respondents chosen through purposive sampling and analyzed it using SmartPLS 4. The results show that lifestyle negatively affects financial stability (β = -0.427; p = 0.000). Social pressure also harms financial stability (β = -0.277; p = 0.001). This study's originality lies in its focus on financial stability as the primary outcome. It examines students' financial behavior through the lenses of behavioral finance and Islamic consumption ethics.